Occurrence of subdural hematomas in Dutch glutaric aciduria type 1 patients - Vester, Marloes E.M. (Eur J Pediatr, 2016)
Patients with glutaric aciduria type 1 (GA1), a rare inherited metabolic disorder, have an increased risk for subdural hematomas (SDHs). GA1 is therefore generally included in the differential diagnosis of children presenting with SDHs. This retrospective cohort study reviews all 25 registered, in the Dutch Diagnosis Registration for Metabolic Disorders, GA1 patients in the Netherlands. This was done between May 2014 and November 2014 to determine the lifetime incidence of SDHs in this population. Seventeen patients were diagnosed either due to clinical symptoms or because of family members with GA1. One out of these 17 had a SDH. This patient showed widened Sylvian fissures on MRI, characteristic for GA1. Eight patients were diagnosed by newborn screening. Three of them had neuroimaging results, and none of them had SDHs. This study shows an overall lower incidence (4.0 %) of SDHs in patients with GA1 than reported in the literature (20–30 %). Conclusion: This finding, in combination with the fact that SDHs in GA1 appear to occur only in the presence of characteristic brain abnormalities on imaging, we recommend that GA1 should not routinely be a part of the differential diagnosis of children with unexplained SDHs in the absence of imaging characteristics suggestive of GA1.